2016
DOI: 10.1108/bpmj-08-2015-0114
|View full text |Cite
|
Sign up to set email alerts
|

Process improvement for professionalizing non-profit organizations: BPM approach

Abstract: Purpose – The purpose of this paper is to present a proposal for process improvement at the Department of Social Responsibility of a Colombian process-based organization, called CAJASAN. The department has four main processes: Foniñez (children fund), Fosfec (unemployment fund), Project Management and International Cooperation and Network Management and Alliances. The objective of this paper is to suggest an improvement in these processes through BPM application. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…In terms of the ambition, we found that 71 methods lead to transactional process change (e.g. [34,35,36]), while only 2 are methods that would enable transformational change [32,37]. On the other hand, we found 18 methods organizations could use that would lead to both transactional and transformational process change (e.g.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In terms of the ambition, we found that 71 methods lead to transactional process change (e.g. [34,35,36]), while only 2 are methods that would enable transformational change [32,37]. On the other hand, we found 18 methods organizations could use that would lead to both transactional and transformational process change (e.g.…”
Section: Resultsmentioning
confidence: 87%
“…Namely, 38 methods are categorized as being analytical, transactional, and inward-looking (e.g. [18,35,36,41,42]). Hence, these are methods that would likely only lead to incremental process improvement.…”
Section: Resultsmentioning
confidence: 99%
“…It's a very difficult challenge for a nonprofit to budget any amount for any reason not related to serving clients, per Haddad et al (2016), who state, "Trade-off between complying with their social values and day-to-day operations: nonprofit organization face continuously trade-off decisions between timely and cost-effective operations performance and the need to serve the society in full, without resource restrictions" (p. 635) [11]. As a result, further studies are needed to examine information technology implementation and organizational readiness factors that enable nonprofit organizations to make budget wise decisions related to information technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, a successful implementation process and plan is crucial. Most nonprofit organizations have very limited budgets and are unable to cover any expenses not related to serving clients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Existe una vasta cantidad de investigaciones sobre la mejora de procesos en diversas organizaciones mediante el uso del BPM. La literatura sobre el tema define que la implementación del BPM como solución de negocio tiene como resultados principales el aumento de las utilidades de la organización a través del mejoramiento de sus productos finales, el mejoramiento de los flujos generales internos y externos de información, la optimización en la eficiencia de los procesos y el incremento de la satisfacción del cliente [13] [14] [15] [10]. Estos resultados son los usualmente perseguidos por los profesionales e investigadores que buscan implementar BPM en sus organizaciones, acompañado, a su vez, de un sentido de madurez organizacional.…”
Section: Estado Del Arteunclassified